1985
DOI: 10.1177/016264348500700102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Systematic Prompting and Prompt Withdrawal to Establish and Maintain Switch Activation in a Severely Handicapped Student

Abstract: A study was conducted to train a five-year-old, severely handicapped boy to activate an adapted battery-operated and electronically controlled toy. To activate the toy the student was required to manually depress a Zygo tread switch which, while depressed, maintained activation of the toy. During the baseline condition the student was provided only with a verbal prompt (and the occurrence of switch activation was recorded). During three subsequent intervention phases verbal prompting only, and verbal and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Results of the Wacker et al study, which demonstrated that 5 students' manipulation of microswitches increased when the manipulation resulted in activation of mechanical toys, suggest that individuals with profound multiple handicaps can provide themselves with leisure entertainment using specific material adaptations. Similar results were reported by Meehan, Mineo, and Lyon (1985), who demonstrated the efficacy of a graduated prompting strategy for teaching a child with profound multiple handicaps to activate a microswitch. Green et al trained education staff to provide functional teaching tasks (instead of more traditional nonfunctional tasks) to their students as well as to manage student involvement with the tasks more efficiently through systematic and frequent prompting and reinforcing of students' attention to the tasks.…”
Section: This Review)supporting
confidence: 85%
“…Results of the Wacker et al study, which demonstrated that 5 students' manipulation of microswitches increased when the manipulation resulted in activation of mechanical toys, suggest that individuals with profound multiple handicaps can provide themselves with leisure entertainment using specific material adaptations. Similar results were reported by Meehan, Mineo, and Lyon (1985), who demonstrated the efficacy of a graduated prompting strategy for teaching a child with profound multiple handicaps to activate a microswitch. Green et al trained education staff to provide functional teaching tasks (instead of more traditional nonfunctional tasks) to their students as well as to manage student involvement with the tasks more efficiently through systematic and frequent prompting and reinforcing of students' attention to the tasks.…”
Section: This Review)supporting
confidence: 85%
“…Twelve studies (Behrmann & Lahm, 1983;Cook, Liu, & Hoseit, 1990;Daniels, Sparling, Reilly, & Humphry, 1995;Dunst, Cushing, & Vance, 1985;Ferrier, Fell, Mooraj, Delta, & Moscoe, 1996;Hanson & Hanline, 1985;Horn & Warren, 1987;Horn, Warren, & Reith, 1992;Light, 1993;Meehan, Mineo, & Lyon, 1985;Sullivan & Lewis, 1990 focused on teaching switch activation use to young children with disabilities in a variety of situations. A majority of the studies used single-subject designs (n = 6) or case study descriptions (n = 2); 4 were noncontrolled group research designs.…”
Section: Switch Interface Device Usementioning
confidence: 99%
“…In addition, children's continued use of the switch provided opportunities to practice the motor response, although in these studies, the motor response used to activate the switch was already in the repertoires of the children. Only one single-subject study reported teaching strategies when the desired response needed to activate the switch was not in the child's repertoire (Meehan et al, 1985). A four-phase approach of systematic prompting and prompt withdrawal techniques was used to successfully teach activation of an adapted toy.…”
Section: Switch Interface Device Usementioning
confidence: 99%
“…May's research documented that the girl learned a cause and effect relationship between her head movement and that recording. The concept of environmental control was demonstrated by Meehan, Mineo, and Lyon (1985), who trained a 5-year-old boy with severe handicaps to activate a battery-powered toy.…”
Section: Program Implementationmentioning
confidence: 99%